1988
DOI: 10.1002/tcm.1770080302
|View full text |Cite
|
Sign up to set email alerts
|

Effect of duration of exposure to benzo(a)pyrene diol‐epoxide on neoplastic transformation, mutagenesis, cytotoxicity, and total covalent binding to DNA of rodent cells

Abstract: We examined the effect of different durations of exposure (20 sec to 24 hr) to (+/-) 7-beta,8 alpha-dihydroxy-9 alpha, 10 alpha -epoxy-7,8,9,10-tetrahydrobenzo(a)pyrene (BPDE I) on the induction of transformation in C3H/10T 1/2 cells and of mutations to 6-thioguanine resistance in Chinese hamster ovary cells (CHO), as well as on BPDE I-DNA binding in these two cell lines. A 20-sec exposure of the cells to BPDE I was sufficient to induce mutations and morphological transformation in vitro. However, the transfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1990
1990
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 20 publications
(7 reference statements)
0
3
0
Order By: Relevance
“…Because BPDE, the active form of benzo[a]pyrene, is used in this assay, the main determinants of the level of induced adducts are carcinogen detoxification and DNA repair capacities of the host cells. Studies have shown that the maximum DNA binding of BPDE is usually accomplished within 15 min of exposure,25 the variation in DNA repair capacity is perhaps the major underlying mechanism responsible for the differences in the levels of the in vitro BPDE‐induced DNA adducts. Indeed, our previous study showed a significant correlation between reduced DNA repair capacity and higher level of BPDE‐induced DNA adducts 6.…”
Section: Discussionmentioning
confidence: 99%
“…Because BPDE, the active form of benzo[a]pyrene, is used in this assay, the main determinants of the level of induced adducts are carcinogen detoxification and DNA repair capacities of the host cells. Studies have shown that the maximum DNA binding of BPDE is usually accomplished within 15 min of exposure,25 the variation in DNA repair capacity is perhaps the major underlying mechanism responsible for the differences in the levels of the in vitro BPDE‐induced DNA adducts. Indeed, our previous study showed a significant correlation between reduced DNA repair capacity and higher level of BPDE‐induced DNA adducts 6.…”
Section: Discussionmentioning
confidence: 99%
“…However, the phase II enzymes had little effect, if any, on the in vitro formation of adducts in this assay. This is because at the relatively large dose (4 μM) of BPDE used and the rapid binding of BPDE to DNA, the level of induced DNA adducts rapidly peaks within 15 min [61] and reduction in the level of induced adducts becomes a function of the host cell repair capacity. A limitation of this study was that the BPDE‐induced adduct levels generated in vitro were 100‐fold higher than the adduct levels generated in vivo, but with a variation of close to 100‐fold in such induced adduct levels rather than a 1,000‐fold often seen in vivo.…”
Section: Ner Phenotype and Cancer Riskmentioning
confidence: 99%
“…A member of a class of environmental pollutants (polycyclic aromatic hydrocarbons) that may contribute to human breast cancer is benzo(a)pyrene (BaP), a major constituent of tobacco smoke (Reynolds et al, 2004). The highly reactive epoxy metabolite of BaP, benzo [a]pyrene diol epoxide (BPDE), can form stable DNA adducts, for example, within Ha-ras oncogene, and initiate carcinogenesis as shown in human fibroblasts and CHO cell lines (Krolewski et al, 1988;Yang et al, 1992). Moreover, there is emerging evidence that indicates that human mammary epithelium may be susceptible to carcinogenic transformation upon exposure to BPDE (Mei et al, 2003).…”
Section: Introductionmentioning
confidence: 99%